DEVELOPMENT AND EVALUATION OF PACLITAXEL LOADED NANOPARTICLES USING 24 FACTORIAL DESIGN - Bhoskar, Manisha; Patil, Priyanka (International Journal of Current Pharmaceutical Research, 2015)
Objective: The aim of this paper was to develop and evaluate of paclitaxel (PTX) loaded bovine serum albumin (BSA) nanoparticals using 24 factorial designs. Methods: Bovine serum albumin nanoparticals prepared by using desolvation technique method followed by spray drying. In the next step, the effect of different formulation variables, including the amount of polymer BSA (A), Tween 80 (B), Glutarldehyde (C) and Speed (D) on the particle size, entrapment efficiency and % cumulative release of drug was investigated. Based on the type and the variables studied, 16 formulations were designed using factorial design method and were then prepared. The prepared antiparticle was characterized for particle size, drug entrapment, and percentage yield, scanning electron microscopy (SEM), Differential scanning calorimetry, zeta potential and in-vitro release study. Results: In order to detect the precise effect of the variables and their interactions, design expert software was used. Among the formulations suggested and based on the predicted responses and their desirability indices two formulations were selected as the optimum formulations and evaluated. Based on in-vitro release study formulations show biphasic release pattern with initial burst effect followed by a slower and sustained release. Conclusion: The result showed that the method was easy and efficient for the entrapment of the drug as well as the formation of spherical nanoparticles.